Reservoir water balance simulation model utilizing machine learning algorithm - Dashti Latif S.; Najah Ahmed A.; Sherif M.; Sefelnasr A.; El-Shafie A. (Elsevier B.V., 2023)
Digital storage; Forecasting; Learning algorithms; Machine learning; Mean square error; Neural networks; Predictive analytics; Water levels; Water quality; ANN prediction; High-efficiency; Radial Basis Function(RBF); Reservoir operation; Reservoir water; Root mean square errors; Test Modeling; Variation of water level; Reservoirs (water)